Crop insurance and pesticide use in European agriculture. (September 2020) - Möhring, Niklas; Dalhaus, Tobias; Enjolras, Geoffroy; Finger, Robert
Abstract: The provision of better risk management tools for farmers and the reduction of adverse effects from pesticide use are both important goals of agricultural policy – but are potentially interrelated and might contradict each other. In this article, we analyze the relation of crop insurance and pesticide use in European agriculture using the examples of France and Switzerland. In our conceptual and empirical framework, we account for the complex structure of insurance uptake, land use and pesticide use decisions of farmers, potentially leading to insurance - pesticide use interactions both at the intensive and extensive margin. Our empirical results indicate a positive and economically significant relation between crop insurance and pesticide use in European agriculture. The findings suggest that without crop insurance, pesticide expenditures would be 6 to 11% lower. However, the importance of extensive and intensive margin relations differs between France and Switzerland and is related to country specific characteristics. We conclude that new risk management instruments should account for potential effects on input use. Highlights: We analyze the relation of crop insurance and pesticide use in French and Swiss agriculture Our analysis accounts for land use change between crops and grassland andchanges of pesticide use per ha of cropland We find a positive relation between crop insurance uptake and pesticide use (+6–11%) The extent of this effect and the main drivers differ across countries